Shigellaflexneri Regulator SlyA Controls Bacterial Acid Resistance by Directly Activating the Glutamate Decarboxylation System - Zhang, Buyu; Ran, Longhao; Wu, Mei; Li, Zezhou; Jiang, Jiezhang; Wang, Zhen; Cheng, Sen; Fu, Jiaqi; Liu, Xiaoyun (Frontiers in Microbiology, 2018)
Shigella flexneri is an important foodborne bacterial pathogen with infectious dose as low as 10-100 cells. SlyA, a transcriptional regulator of the MarR family, has been shown to regulate virulence in a closely related bacterial pathogen, Salmonella Typhimurium. However, the regulatory role of SlyA in S. flexneri is less understood. Here we applied unbiased proteomic profiling to define the SlyA regulon in S. flexneri. We found that the genetic ablation of slyA led to the alteration of 18 bacterial proteins among over 1400 identifications. Intriguingly, most down-regulated proteins (whose expression is SlyA-dependent) were associated with bacterial acid resistance such as the glutamate decarboxylation system. We further demonstrated that SlyA directly regulates the expression of GadA, a glutamate decarboxylase, by binding to the promotor region of its coding gene. Importantly, overexpression of GadA was able to rescue the survival defect of the slyA mutant under acid stress. Therefore, our study highlights a major role of SlyA in controlling S. flexneri acid resistance and provides a molecular mechanism underlying such regulation as well.